Indicative tests for cracked asphalt pavement sealant performance [electronic resource] - Halmat Gharib Khidhir, 1977- (2012)
Thesis (Sarjana (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2012